2013
DOI: 10.1039/c2dt31014g
|View full text |Cite
|
Sign up to set email alerts
|

Self-assembled metalla-rectangles bearing azodipyridyl ligands: synthesis, characterization and antitumor activity

Abstract: Sixteen arene-Ru based molecular-rectangles were self-assembled in high yields by the equimolar mixing of arene-Ru acceptors (Aa-Ad) with various azopyridyl ligands (1,2-di(pyridyl-4yl)diazene (L1), 1,2-bis(pyridin-4-ylmethylene)hydrazine (L2), 1,2-bis(1-(pyridin-4-yl)ethylidene)hydrazine (L3), 1,2-bis(pyridin-4-ylmethylene)hydrazine (L4)) in nitromethane-methanol solutions. These new molecular-rectangles were fully characterized by a host of analytical techniques including elemental analysis, (1)H and (13)C N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 48 publications
(26 citation statements)
references
References 62 publications
0
26
0
Order By: Relevance
“…The IC 50 values of the corresponding clips were significantly higher, with only the donq clip showing measurable activity for SK-hep-1 cells. 23 The donq-based SCCs were particularly potent, with IC 50 values oftentimes exceeding that of cisplatin, and on par with a second control drug, doxorubicin. The oxalato and dobq-containing species were relatively inactive in comparison.…”
Section: Ruthenium Sccs As Anticancer Agentsmentioning
confidence: 99%
See 1 more Smart Citation
“…The IC 50 values of the corresponding clips were significantly higher, with only the donq clip showing measurable activity for SK-hep-1 cells. 23 The donq-based SCCs were particularly potent, with IC 50 values oftentimes exceeding that of cisplatin, and on par with a second control drug, doxorubicin. The oxalato and dobq-containing species were relatively inactive in comparison.…”
Section: Ruthenium Sccs As Anticancer Agentsmentioning
confidence: 99%
“…For example, by incorporating amide groups into the core of dipyridyl donors, 17 and 18 , 25 sites for hydrogen bonding were preserved and the presence of azo functionalities on donors 19 – 22 unlock potential photo-sensitization. 23 The assemblies formed from the combinations of 17 – 22 with 6 – 9 were investigated using five cell lines obtained from American Type Culture Collection for SCC25-SCC27 : HeLa, HCT-15, and MDA-MB-231, SK-hep-1, A-549, with the latter two cell lines also used in assays with the sixteen azodipyridyl-based assemblies. SCC25 and SCC26 , containing the oxalate bridged clip, were inactive, while rectangle SCC27 , which employed the donq-bridged clip, possessed IC 50 values that were similar to those of cisplatin, with values (µM) of 4.2 ± 0.11 (SK-hep-1); 10.2 ± 0.21 (HeLa); 3.7 ± 0.10 (HCT-15); 3.2± 0.11(A-549); 2.8 ± 0.03 (MDA-MB-231).…”
Section: Ruthenium Sccs As Anticancer Agentsmentioning
confidence: 99%
“…Following these first studies, Chi, Stang and coworkers have reported several analogous metalla-rectangles, each being formed by combining dinuclear arene ruthenium clips and bipyridyl connectors [39,[61][62][63][64][65]. The IC 50 values for particular combinations of clips and connectors are in the lower micromolar range, while others show poor activities.…”
Section: Water-soluble Arene Ruthenium Complexesmentioning
confidence: 99%
“…3 Recently, a variety of arene-Ru molecular clips bridged by O,O-chelating ligands have been reported for the self-assembly of metalla-rectangles and prisms. 4 In this context, ruthenium is not simply a structural element; the metal fulfils a functional role as the impetus for antitumor activity. 5 …”
mentioning
confidence: 99%